Policy Analysis of Nature Tourism Management Based on Village Owned Enterprises (BUMDes) in Empowering the Community Economy in Taman Dadapan, Tulungagung Regency - Nunun Nurhajati; Anang Sugeng Cahyono; Mohammadtahir Cheumar (Universitas Merdeka Malang, 2026)
Village tourism management based on VillageOwned Enterprises (BUMDes) is one of the steps taken by village governments to maximize local potential in order to improve community welfare. This study aims to analyze the implementation of BUMDesbased natural tourism management policies in empowering the community’s economy at Dadapan Tourism Park, Tulungagung Regency. This study applies a qualitative method with a literature review approach and public policy analysis based on George C. Edward III’s policy implementation theory, which includes communication, resources, disposition, and bureaucratic structure. The research findings indicate that the management of Dadapan Tourism Park by BUMDes Raharja has successfully provided positive impacts on community economic empowerment, including the emergence of local business opportunities, increased community income, and the absorption of labor in the tourism area. However, tourism management still faces several challenges, such as limited human resources, less effective tourism promotion, and a lack supporting tourism facilities. Therefore, strengthening BUMDes management, improving tourism promotion, and providing infrastructure support are needed so that village tourism management can grow sustainably.